2021
DOI: 10.1177/2055207621996876
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health approaches to disease surveillance in Africa; Wellvis COVID triage tool

Abstract: COVID-19 has rapidly spread across the globe and was declared a pandemic by the World Health Organization (WHO). The COVID-19 infection continues to spread across Africa. In Africa, mobile phone applications have been used for the surveillance and reporting of infectious diseases such as malaria, measles, polio, and other notifiable diseases as mandated by the WHO. A good example is the early warning alert and response system. We developed an eight-question triage tool using the Nigerian Centre for Disease Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“… 65 There is a growing interest in Africa to implement participatory surveillance systems in response to COVID-19. For instance, digital platforms and mobile apps have been developed in Nigeria, 66 Ethiopia, 67 and Kenya 68 to facilitate case reporting, symptoms reporting, and risk communication.Data gotten through participatory surveillance can also clarify changes in health-seeking behaviour while interpreting facility-based surveillance data. 9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 65 There is a growing interest in Africa to implement participatory surveillance systems in response to COVID-19. For instance, digital platforms and mobile apps have been developed in Nigeria, 66 Ethiopia, 67 and Kenya 68 to facilitate case reporting, symptoms reporting, and risk communication.Data gotten through participatory surveillance can also clarify changes in health-seeking behaviour while interpreting facility-based surveillance data. 9…”
Section: Resultsmentioning
confidence: 99%
“…87,88 Many African countries are already implementing participatory digital apps for COVID-19 contact tracing, reporting of symptoms, and other surveillance parameters. [66][67][68] The meddlesome nature of this approach is concerning, especially for public health and legal ethics. 88 For instance, in Nigeria 89 and South Africa 90 concerns have been raised regarding the use of digital tools for surveillance.…”
Section: Burden Of Co-epidemic Surveillancementioning
confidence: 99%
“…The post hoc analysis allowed us to identify the areas that need further exploration. Besides, the predictive analytics allowed us to quantify the impact of COVID-19 on the development of new H-F apps 8 . The availability of more than expected apps indicates the greater need for these apps during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Technology has played a pivotal role in maintaining H-F activities during the pandemic through mHealth (mobile health) and mobile apps. 6,7 Mobile apps and smart technologies have not just assisted in containing the pandemic [8][9][10][11][12] but also in motivating users to keep track of their H-F activities, as observed by Panicker and Chandrasekaran. 13 For instance, Sorkin et al 14 reported increased use of digital technologies, including mobile apps for stress management during COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Tools studied were mostly located in the United States (6/22, 27%) [3,10,11,19,24,25]. A total of 12 studies were conducted in other countries, including France (3/12, 25%) [13,15,26], Iran (1/12, 8%) [27], Denmark (1/12, 8%) [28], China (1/12, 8%) [29], Nigeria (1/12, 8%) [30], Ireland (1/12, 8%) [31], Greece (1/12, 8%) [32], Finland (1/12, 8%) [33], Canada (1/12, 8%) [6], and Switzerland (1/12, 8%) [14]. Furthermore, 4 studies were conducted in >1 country, with 1 study conducted in the United States, India, Nepal, and Bangladesh [34]; 1 study conducted in the United States, Japan, Singapore, and the United Kingdom [12]; and 2 studies conducted worldwide [35,36].…”
Section: Location Of Included Studiesmentioning
confidence: 99%